Digital Writing Assistance in EFL Contexts: A Study on Grammarly Use by Indonesian Students - Rahmatika, Tia (Journal of Language Intelligence and Culture, 2025)
This study investigates the efficacy of Grammarly, an automated writing assistance tool, in enhancing the writing proficiency of EFL students at UINSI Samarinda. Fifty third-semester students participated and were divided into two groups: an experimental group receiving instruction supplemented by Grammarly and a control group following conventional writing instruction without technological support. The analysis employed a quasi-experimental design comparing growth scores, defined as the difference between pre-test and post-test scores for each student. Both groups showed normal distribution (Shapiro-Wilk, p > 0.05) and homogeneity of variances for pre- and post-test scores (Levene’s test, p > 0.05), except for the improvement scores, which violated homogeneity (p = 0.000). The Grammarly-assisted group improved significantly more (pre-test M = 59.48, post-test M = 84.16) than the control group (pre-test M = 56.28, post-test M = 65.28), with a mean improvement difference of 15.68 points (t = -9.847, p = 0.000). The effect size was small to moderate (Cohen’s d ≈ 0.34). These findings suggest that Grammarly provides effective support in developing EFL writing skills and underscore the need for further research on student perceptions of digital writing tools in language education.